Analyis Penataan Fasilitas dan Lanskap Sesuai dengan Permenparekraf No 4 Tahun 2021 di Teras Sejiwa Café - Yanti, Dewi (Jurnal Akademi Pariwisata Medan, 2024)
Landscape is stated as a land that has certain forming elements, composition and characteristics as its differentiator. (Dina et al., 2005) According to Eckbo in his book entitled "Lanscape for Living" landscape as part of the land area built or formed by humans outside buildings, roads, utilities, to the wild nature which is designed primarily as a place for humans to live. According to Simon (19983) landscape is a natural landscape that has certain characteristics that can be enjoyed through all the senses that humans have.